2005
DOI: 10.1002/cncr.21489
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and the family: An integrative model

Abstract: The stresses and uncertainties of cancer can be overwhelming for families. The Family System Illness model offers a psychosocial map to address these challenges and to make the inevitable strains more manageable. It provides a set of terms and a common language within a framework that attends to the longitudinal, psychosocial pattern of a health condition within a multigenerational, life cycle, and belief system context. Such a psychosocial framework can facilitate collaborative, effective coping and adaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
0
14

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 39 publications
(29 reference statements)
6
121
0
14
Order By: Relevance
“…Rolland discusses the challenges that cancer presents for families and offers a richly illustrated and dynamic Family Systems-Illness Model that he asserts can offer a psychosocial map with which to address these challenges and make the inevitable strains more easily managed. 10 In the next set of four articles, the authors explore the efficacy of interventions delivered at different points in the cancer trajectory to improve survivors' coping and health. A provocative 1989 study by Spiegel et al 11 suggested that participation by women with metastatic breast cancer in a weekly support group not only promotes psychologic adaptation, but also might prolong the lives of the participants.…”
mentioning
confidence: 99%
“…Rolland discusses the challenges that cancer presents for families and offers a richly illustrated and dynamic Family Systems-Illness Model that he asserts can offer a psychosocial map with which to address these challenges and make the inevitable strains more easily managed. 10 In the next set of four articles, the authors explore the efficacy of interventions delivered at different points in the cancer trajectory to improve survivors' coping and health. A provocative 1989 study by Spiegel et al 11 suggested that participation by women with metastatic breast cancer in a weekly support group not only promotes psychologic adaptation, but also might prolong the lives of the participants.…”
mentioning
confidence: 99%
“…16 The ability of spouses to understand the communicative intent and meaning was perceived by the persons with MND as important in the maintenance of social closeness. Reports in the literature allude to the importance of both verbal and nonverbal communication in the maintenance of marital communication, 16,17,24 but the value of nonverbal communication in maintaining social closeness in the face of decreased verbal communication cannot be underestimated and is supported by the findings of previous studies. 20,25 The inevitable progressive decline in the speech abilities of persons with MND, despite the type of onset, confirms reports in the literature.…”
Section: Discussionmentioning
confidence: 89%
“…16 Sensitive, open, and direct communication plays a central role in marriage and is essential for couples to cope with chronic illness. [15][16][17] The ability of spouses to listen, to express themselves clearly and accurately and to understand each other is critically important in marital communication. 18 This is achieved by the key characteristics of marital communication, namely verbal (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that this model offers a collaborative practice between professionals and families to aid coping and adaptation. This model has been applied to a number of illnesses, including families facing genetic conditions and cancer [23][24] and may have relevance within CLP, at significant times within the treatment journey, such as the surgery. Resilience has begun to be studied within CLP, but initial studies have been focussed on the resilience of the individuals born with CLP themselves [5,25] rather than their families.…”
Section: Resiliencementioning
confidence: 99%